A Sharper Computational Tool for Regression. Issue 1 (2nd January 2023) - Liu, Xiaoqian; Chi, Eric C.; Lange, Kenneth
Abstract: Building on previous research of Chi and Chi, this article revisits estimation in robust structured regression under the L 2 E criterion. We adopt the majorization-minimization (MM) principle to design a new algorithm for updating the vector of regression coefficients. Our sharp majorization achieves faster convergence than the previous alternating proximal gradient descent algorithm by Chi and Chi. In addition, we reparameterize the model by substituting precision for scale and estimate precision via a modified Newton's method. This simplifies and accelerates overall estimation. We also introduce distance-to-set penalties to enable constrained estimation under nonconvex constraint sets. This tactic also improves performance in coefficient estimation and structure recovery. Finally, we demonstrate the merits of our improved tactics through a rich set of simulation examples and a real data application.